A child's introduction to Greek mythology : the stories of the gods, goddesses, heroes, monsters, and other mythical creatures - Alexander, Heather, 1967-; Hamilton, Meredith (New York : Black Dog & Leventhal Publishers, 2011)
Introduces children to the gods and goddesses of Greek mythology, describing how the Greeks used mythology to explain things they did not understand about the world around them.
May include a Greek mythology family tree poster, stickers, and temporary tattoos.
Includes bibliographical references (p. 96) and index.
5.7
3-6.
3-6
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Greek; Greek mythology